Indigenous epistemologies of childhood in contexts of inequality: Three case studies from the "Global South". (August 2022) - Amigó, María Florencia; García Palacios, Mariana; Enriz, Noelia; Hecht, Ana Carolina
Drawing on long-term ethnographies with children, the authors (anthropologists from the "Global South") problematize the disconnect between homogenising discourses around "childhood", and the localised, socio-culturally rich experiences of indigenous children. Through an anthropological lens in dialogue with post-colonial theory they explore vernacular conceptualisations and practices around childhood in three indigenous communities –two in Argentina, one in Indonesia. In doing so, they place these childhoods within local, regional and global forces, highlight contexts of inequality, and explore children's active positionality in such contexts.